Instrumento para a introdução da abordagem da eficiência energética em cursos de engenharia civil - Cesar, Luiza Denardi (Universidade Federal de São Carlos, 2011)
This study aims to build a tool for evaluating energy efficiency and insert it in disciplines of Civil Engineering courses. The instrument was constructed by applying the criteria for certification of sustainable construction in Brazil: High Environmental Quality, Energy Efficiency Labeling of buildings and Seal Blue House CASH. An investigation of the status in the Civil Engineering courses was performed based on information gathered from, either syllabuses, or programmatic content of the disciplines. This investigation included the curriculum established by the Resolution CNE/CES N. 11, which points out the National Curriculum Guidelines of an undergraduate degree in engineering. The higher education institutions were selected based on courses in Civil Engineering, which were evaluated in 2008 by the National Survey of Student Performance. In addition, in the process of selecting courses, only the courses with pedagogical project or curriculum which shows at the webpage the notes or syllabus of the courses was considered. Following these criteria, 15 courses of Civil Engineering were selected. The results show that it is difficult to separate the content of the subjects according to the core content. This situation may be the reason for the average workload of the core of basic and professional contents in both biannual and annual periodicities courses be larger than the requirements of the Guidelines National Curriculum. On the other hand, for the specific content core, it was observed the opposite in both periodicities. In this case there was difficulty in separating the content according to the core content. In addition, the courses of Civil Engineering still do not use the possibility of curricular flexibility allowed by these Guidelines. The reduced number of disciplines that include energy efficiency indicated that the educational institutions are not taking advantage of the possibility of introducing new up to date and important topics in the engineer formation, such as energy efficiency.
Keywords: Construção civil; Engenharia - estudo e ensino; Ensino superior - sustentabilidade; Poluição; Engineering education; Sustainable engineering; Environmental pollution; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL